2017
DOI: 10.1155/2017/1717492
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Pseudomonas aeruginosa Community-Acquired Pneumonia: A Case Report and Review of the Literature

Abstract: Lung cavities are not typically associated with community-acquired pneumonia (CAP). CAP due to P. aeruginosa is rare and even less commonly causes necrotizing pneumonia. We report a case of P. aeruginosa CAP that progressed to necrotizing pneumonia and was eventually fatal. Procalcitonin (PCT) has been well investigated in guiding antibiotic therapy (especially CAP) in adults. In this case, PCT at presentation and sequentially was negative. We discuss this caveat and present hypotheses as to the sensitivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…It is a common pathogenic bacteria in hospital acquired pneumonia, and is usually seen in patients who have structural lung disease, or are immunocompromised [1] . However, it is rarely identified as a cause of pneumonia in previously healthy individuals, accounting for 0.4-6.9% of the reported cases of CAP requiring hospitalization [2] and 1.8-8.3% CAP requiring intensive care unit (ICU) admission [3] . Several studies [4,5] found that fatal P. aeruginosa pneumonia in healthy patients was associated with exposure to contaminated hot tubs.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common pathogenic bacteria in hospital acquired pneumonia, and is usually seen in patients who have structural lung disease, or are immunocompromised [1] . However, it is rarely identified as a cause of pneumonia in previously healthy individuals, accounting for 0.4-6.9% of the reported cases of CAP requiring hospitalization [2] and 1.8-8.3% CAP requiring intensive care unit (ICU) admission [3] . Several studies [4,5] found that fatal P. aeruginosa pneumonia in healthy patients was associated with exposure to contaminated hot tubs.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we found 13 cases of necrotizing CAP due to P. aeruginosa associated with cavitation. Table 1 summarizes the 11 most recent cases [[1], [2], [3], [4], [5], [6], [7], [8], [9], [10]]. The main risk factors for necrotizing CAP due to P. aeruginosa are: lung structural abnormalities (including cystic fibrosis, emphysema, bronchial dilatation, chronic obstructive pulmonary disease), immunocompromised condition (including neoplasia, neutropenia, prolonged antibacterial therapy, immunosuppression), and exposure to contaminated liquids (including hot tub, spa, humidifier) [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding antimicrobial management for CAP, the literature is summarized in Table 1 [[1], [2], [3], [4], [5], [6], [7], [8], [9], [10]]. It is generally not appropriate to administer empiric anti-Pseudomonas therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a paucity of data regarding the emergence, incidence, progression, and outcome of pseudomonas lung infection. There is also no established explanation on the predilection of lung involvement, although the infection foci favours upper lobes of the lung postulated due to increased ventilation and perfusion ratio and less effective lymphatic drainage .…”
Section: Discussionmentioning
confidence: 99%